2005
DOI: 10.1002/jmri.20344
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient measurements with diffusion‐weighted magnetic resonance imaging for evaluation of hepatic fibrosis

Abstract: Purpose:To evaluate the use of apparent diffusion coefficient (ADC) measurements based on diffusion-weighted MRI (DWI) to assess stage of liver disease. Materials and Methods:A total of 31 patients who underwent both a liver biopsy and DWI and 132 patients who only underwent DWI were enrolled. Biopsy specimens were scored for fibrosis and necroinflammation according to the Knodell histology activity index (HAI). The 31 patients consisted of 21 patients with chronic hepatitis and 10 with cirrhosis (ChildPugh st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
152
1
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(171 citation statements)
references
References 20 publications
11
152
1
7
Order By: Relevance
“…Furthermore, The R2-ADC values for each fibrosis stage did not show a tendency to increase or decrease. This result was different from those of Lewin et al and Koinuma et al [14,15] showing that ADC values for fibrotic liver decreased as the severity of liver fibrosis increased; on the contrary, our results were similar to those of other investigations indicating that ADC values do not decrease as the fibrosis scores increase [16,32,33].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, The R2-ADC values for each fibrosis stage did not show a tendency to increase or decrease. This result was different from those of Lewin et al and Koinuma et al [14,15] showing that ADC values for fibrotic liver decreased as the severity of liver fibrosis increased; on the contrary, our results were similar to those of other investigations indicating that ADC values do not decrease as the fibrosis scores increase [16,32,33].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, recent improvements in MRI technology have made it feasible to apply diffusion-weighted MRI (DW-MRI) to abdominal imaging. Although several recent studies have reported that DW-MRI can assess liver fibrosis using apparent diffusion coefficient (ADC) values [14,15], conflicting results have been also reported and data on intra-and interobserver reliability of DW-MRI has not yet been evaluated [16].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusing water spins within a voxel experience phase dispersion, causing signal attenuation that is dependent on the (12,17,18,47,50), and for liver tumor treatment response (6,11,14,20,(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…If two or more diffusion-weighted images are obtained, then it is possible to calculate the apparent diffusion coefficient (ADC) of water protons in tissues, which is determined by the slope of the log intensity versus b value. 39,40 The calculated ADC values can be displayed as an image and quantitative analysis can be performed by placing measuring the mean value within a region of interest, which is typically positioned in the right hepatic parenchyma to avoid major vascular structures.…”
Section: Novel Mr Applications For In Vivo Detection Of Hepatic Fibrosismentioning
confidence: 99%